Shock wave lithotripsy in the era of COVID-19 - Rabie M Ibrahim; Faysal Elzawy; Ahmed Mohamed Ragheb; Akram A Elmarakbi; Osama Sayed; Amr M Lotfy; Ahmed Youssef; Hany F Badwy; Ahmed Gamal Mohamed (Urology Annals, 2024)
Objective: The objective of the study y was to evaluate factors which can improve shock wave lithotripsy (SWL) results to keep up with COVID-19 pandemic. Methods: Between June 2020 and June 2021, patients with radio-opaque or faint radio-opaque upper urinary tract stones, stone attenuation value ≤1200 HU, and stones size <2.5 cm were treated by electrohydraulic SWL. Patients with respiratory tract symptoms elevated temperature, contact with COVID-19 patients, or positive COVID-19 swab 2 weeks preoperatively, skin-to-stone distance >11 cm, and body mass index >30 kg/m2 were excluded from the study. Patients were prospectively enrolled in SWL done at a rate of 40–50 SWs/min under combined ultrasound and fluoroscopy-guided, ramped into high power in the 1st 300 shocks. Success rate and complications were recorded. Results: Five hundred and ninety patients completed the study. The success rate after 1st session was 408/590 patients (69.15%) which was augmented by 2nd session to reach 527/590 patients 89.3%. The success rate was 96.2% at 3 months postoperatively. Most complications were mild (Grade 1 or 2). Conclusions: SWL results improved using slow rate high power from the start of the session under combined fluoroscopy and ultrasound guidance. SWL may be a preferred option during a pandemic.